Effect of nitrogen levels and herbicides on productivity and economics of sesame (Sesamum indicum) and residual effects on succeeding chickpea (Cicer arietinum) - SUNITA; BAIRWA, R C; NITHARWAL, PRAVEEN KUMAR; GODARA, A S; REAGAR, M L; SHARMA, ASHISH KUMAR (The Indian Journal of Agricultural Sciences, 2026)
During the 2022–23 and 2023–24, a field experiment was carried out in loamy sand soil, aimed to investigate the effect of nitrogen levels and different herbicides on weed dynamics, growth and productivity of sesame (Sesamum indicum L.) and their residual effects on succeeding chickpea (Cicer arietinum L.). Twenty different treatment combinations were tested in the study. The main-plots were assigned four different nitrogen levels (control, 20, 40, and 60 kg/ha) and the sub-plots were divided into five different weed control methods. The weed-free treatment, pendimethalin @ 750 g/ha pre-emergence, flumioxazin @ 75 g/ha pre-emergence, imazethapyr @ 50 g/ha applied 25 days after sowing, and weedy check were the weed control interventions. During the Rabi seasons, chickpea was grown as a succession crop after the sesame harvest to evaluate the residual effects of the applied treatments. The results demonstrated that applying 40 kg N/ha significantly enhanced multiple growth metrics. These metrics included plant height, dry matter accumulation, crop growth rate, relative growth rate, seed yield (594 kg/ha), stalk yield (2,262 kg/ha) and oil content (46.78 %) of sesame but it was at par with 60 kg/ha. The seed yield % increased by 68.4 and 18.5 %, net return (42,533 ₹/ha) registered 216.5 and 35.9 % increase over control and 20 kg N/ha, respectively and a benefit-cost ratio maximum (2.39) was recorded with the application of nitrogen 60 kg/ha, which was at par with 40 kg N/ha (2.29). Among herbicide treatments pendimethalin at 750 g/ha, showed a significant improvement in plant height, dry matter accumulation, crop growth rate, relative growth rate, seed yield (770 kg/ha), stalk yield (2,931 kg/ha), net return (67,609 ₹/ha), and benefit-cost ratio (3.28) of sesame over flumioxazin @75 g/ha, weedy check and imazethapyr @50 g/ha, whereas it is at par with weed free treatment. Maximum partial factor productivity (25.05 kg/kg), agronomic efficiency (7.42 kg/kg) and physiological efficiency (29.95 kg/kg) was observed in 20 kg N/ha followed by 40 kg N/ha and 60 kg N/ha. Lowest weed index was reported under pendimethalin at 750 g/ha (5.18 %), however highest weed control efficiency (88.50 %) was observed under imazethapyr @50 g/ha. Furthermore, the succeeding chickpea crop was unaffected by the nitrogen and herbicide that had been sprayed in pervious chickpea crop. It was concluded from a two-year study that the application of nitrogen at 40 kg/ha along with pendimethalin at 750 g/ha as a pre-emergence treatment is recommended for reduce weed dynamics and achieving higher productivity, along with improved quality and profitability, in the hyper-arid regions of Rajasthan, considering its economic importance.